The parliament of man : the United Nations and the quest for world government - Kennedy, Paul M., 1945- (London : Penguin, 2007)
Can the world be governed by agreement rather than conflict? In 1945 the world's powerful nation states came together to 'save succeeding generations from the scourge of war and reaffirm faith in the fundamental human rights'. This title tells the story of the UN - its creation, the threats it has faced, and possibilities it holds for the future.
Includes index.
Originally published: London: Allen Lane, 2006.
Keywords: 20151000; International relations; Relaciones internacionales; United Nations -- History; United Nations. -- 1945-